FEMINIST VISUAL-LINGUISTIC ANALYSIS OF AKO AY MAY KIKI - Valenzuela, Christian Loid; Dinoy, Danilo (International Journal of Humanity Studies (IJHS), 2025)
This study employs feminist literary theory and a visual-linguistic analysis to examine the portrayal of femininity in the children’s illustrated storybook Ako ay May Kiki by Glenda C. Oris. It analyzes how linguistic choices, based on Abram’s (1999) typology of diction, and the use of color, guided by the principles of color psychology, contribute to the construction of female representation. Findings reveal that the storybook challenges stereotypes of women as passive through active verbs that depict the female protagonist as strong and assertive. The explicit use of anatomical terms such as “vagina” normalizes discussions of the female body by presenting it as natural and empowered. The minimal use of adjectives and reliance on concrete, everyday language frame femininity in practical terms. Visually, the deployment of warm, positive colors conveys body acceptance and empowerment, while neutral tones reflect inclusivity and authenticity. Furthermore, the use of green and blue—commonly associated with masculinity—subverts conventional gender coding and broadens the representation of femininity. By highlighting inclusive language and visual strategies, the study underscores how the text and illustrations facilitate body consciousness, gender sensitivity, and positive self-esteem among children.